PENGARUH KUALITAS PELAYANAN PERSEPSI HARGA DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN PADA TAMAN JAGUNG RESIDENCE - Wulandari, Indah; Astuti, Nelly; Novika (Jurnal Progresif Manajemen Bisnis, 2022)
This research was entitled: “Pengaruh Kualitas Pelayanan, Persepsi Harga Dan Citra Merek Terhadap Kepuasan Konsumen pada Taman Jagung Residence ”. This study is a survey using a questionnaire as an instrument. The population used in this study were consumers at Taman Jagung Residence and taken as many as 85 respondents using simple random sampling, a sample selection random sampling of the population without regard to the strata that exist in the population. Validity and Reliability test using Cronbach Alpha. The analysis technique used is multiple regression analysis. This study aims to determine the effect of (1) Quality Of Service on Cunsumer Satisfaction at Taman Jagung Residence, (2) Perceptions Of Price on Cunsumer Satisfaction at Taman Jagung Residence, (3) Brand Image on Consumer Satisfaction at Taman Jagung Residence, and (4) Service Quality, Perceptions of Price, and Brand Image on Consumer Satisfaction at Taman Jagung Residence. The study found that : (1) Quality of service had a positive and significant effect on Consumer Satisfaction with a t-count value of 6.732 > t-table 1.66342 (2) Price Perception had a positive and significant effect on Consumer Satisfaction with a t-count value of 2.277 > t-table 1.66342 (3) Brand Image had a positive and significant effect on Consumer Satisfaction with a t-count value of 7.006 > t-table 1.66342 (4) Service Quality, Price Of Perception, and Brand Image simultaneously have a positive and significant effect with an F value of 192.984 > F-table 2.72 (5) The result of adjusted R Square is 87.3%, which indicates that 87.3% of Service Quality, Price Perception, and Brand Image variables have a positive and significant effect on consumer satisfaction and the remaining 12.7% is influenced by variables not used in this study.